THE EFFECT OF MEMBER PARTICIPATION, NUMBER OF MEMBERS AND CAPITAL ON THE SUCCESS OF COOPERATIVE BUSINESS: PENGARUH PARTISIPASI ANGGOTA, JUMLAH ANGGOTA DAN PERMODALAN TERHADAP KEBERHASILAN USAHA KOPERASI - Lora Wita (Yayasan Education and Social Center, 2022)
This study aims to determine the effect of member participation, total member, and equity on the bussines success in DKI Jakarta in 2016-2019. Research method in this study is panel data from 2016 to 2019 in thirteen cooperative with quantitative descriptive method. Data collected by each year from annual report . The results of this study indicate that partially the participation of member variabel , total member and equity have a significant effect on bussines success indicated by the probability value of more greater than the alpha value (0.05). Simultaneously all the research variables have a significant effect on bussines succes and have an effect that is shown through R2 of 95.02% indicating that variabel of participation of member. Tottal member and equity can explain the Y variable , the remaining 4.98% is explained by other variabels outside the research variable